Impact of IT Sophistication and User Technical Proficiency on Accounting Information System Effectiveness (E-Jurnal Akuntansi, 2025)
This research was conducted at LPD Kecamatan Ubud with the aim of analyzing the influence of personal technical skills and the sophistication of information technology on the effectiveness of accounting information systems. The research population includes all accounting staff in 32 LPD Kecamatan Ubud, with a sample of 96 respondents consisting of accounting and finance staff. Data was collected through questionnaires, and data analysis was carried out using multiple linear regression methods. The initial steps of the research included testing the validity and reliability of the research instruments. The analysis results indicate that the sophistication of information technology significantly enhances the effectiveness of accounting information systems. Additionally, personal technical skills also have a significant influence and positively impact the effectiveness of the system.
Keywords: Sophistication of Information Technology; Personal Technical Ability; Effectiveness of Accounting Information Systems